UPAYA PENCEGAHAN RISIKO PERDARAHAN PASIEN DEMAM BERDARAH DENGUE DI RSUD dr. SOEHADI PRIJONEGORO - Astuti, Mila Dwi Astuti; , Arief W. Jadmiko, S.Kep., Ns., M.Kep (2016)
Background: Dengue haemorrhagic fever (DHF) was initially caused by the bite of Aedes Aegypti mosquito that circulate into the human body, dengue virus infection forming antigen-antibody complexes that activate the complement system so that the increased membrane permeability that causes latelet aggregation, plasma leakage and activate coagulation via endothelial damage vessels blood. Sticking to the antigen-antibody complexes in platelet membrane stimulate spending ADP (Adenosin diphospat) which causes cells platelets from sticking together and then destroyed by the reticuloendothelial resulting thrombocytopenia (blood clotting factors) thus causing the risk of bleeding. Objective: Provide an overview of nursing care in patients DHF by preventing the risk of bleeding by standard nursing. Methods: The author uses descriptive method in this case study research, by collecting data at 28 March 2016. Sources of assessment data obtained from observation, interviews autoanamnesa and alloanamnesa such patients, families, nursing notes and study the literature. Results: After nursing actions during 3x24 hours include nursing care such as a monitor signs of bleeding, monitor laboratory values, vital sign monitor, monitor fluid status, instruct the patient to rest, instruct the patient consume red guava juice to prevent the risk of bleeding, collaboration with the doctor in medicine. The result obtained are the patients condition began to improve, not bleeding, the patient's vital signs normal, increased platelet value. Coclusion: The issue of nursing at the risk of bleeding associated with blood clotting factors (thrombocytopenia) can be resolved in part, it would require further treatment and cooperation with other health professionals. Patients and families are needed in the succes of nursing care. On the non pharmacological therapy by providing red guava juice to DHF patients can be influenced to increase the platelet count of the patient.